Comparison of rumination between men and women with obsessive- compulsive disorder and social anxiety disorder: a cross-sectional study - Salek Ebrahimi, Leila; Mousavi, Seyedeh; Belal Habashi, Soheila; Hasani , Jafar (Researcher Bulletin of Medical Sciences, 2020)
Introduction: Ruminations are one of the influencing factors in the development and continuation of obsessive-compulsive disorder and social phobias. Therefore, this study aimed to compare the rumination between man and women with obsessive-compulsive disorder and social anxiety. Materials & Methods: The research design was cross-sectional. The research participants included 30 patients with social anxiety disorder and 30 patients with obsessive-compulsive disorder who were aged between 15 and 50 years from Zanjan city in 2017. Samples were selected on the basis of psychiatrist diagnosis and structured diagnostic interviews (SCID-I) and (SCID-II), and the inclusion and exclusion criteria. The rumination response style questionnaire (RRS) was used to measure the variables. Results: The results of MANOVA showed that women with OCD have more rumination and distraction than men with this disorder (p≤0.05). However, there was no significant difference between two groups regarding the component of contemplation. There was no significant difference between men and women in social anxiety disorder in terms of rumination and its related components. Conclusion: According to research findings, rumination plays an important role in obsessive-compulsive disorder and social anxiety, which are experienced by both groups. Therefore, the role of ruminations in women with obsessive-compulsive disorder is more intense.